Living Among Giants : Exploring and Settling the Outer Solar System - Carroll, Michael (Springer International Publishing : Imprint: Springer, 2015)
The outer Solar System is rich in resources and may be the best region in which to search for life beyond Earth. In fact, it may ultimately be the best place for Earthlings to set up permanent abodes. This book surveys the feasibility of that prospect, covering the fascinating history of exploration that kicks off our adventure into the outer Solar System.   Although other books provide surveys of the outer planets, Carroll approaches it from the perspective of potential future human exploration, exploitation and settlement, using insights from today's leading scientists in the field. These experts take us to targets such as the moons Titan, Triton, Enceladus, Iapetus and Europa, and within the atmospheres of the gas and ice giants. In these pages you will experience the thrill of discovery awaiting those who journey through the giant worlds and their moons.   All the latest research is included, as are numerous illustrations, among them original paintings by the author, a renowned prize-winning space artist.